A study of transfer and prevalence of organic gunshot residues. (August 2017) - Hofstetter, Carmen; Maitre, Matthieu; Beavis, Alison; Roux, Claude P.; Weyermann, Céline; Gassner, Anne-Laure
Highlights: Study of the distribution of OGSR on the shooter using a pistol. High variability in OGSR production and transfer. OGSR are not only transferred to the hand of the shooter, but also to other parts of the upper body. The amount of OGSR is not proportional to the number of discharges. Probability of occurrence of OGSR in the general population is low. Abstract: The main goal of the present study was to determine the amounts and distribution of organic gunshot residues (OGSR) on the shooter's upper body and clothing after discharging a pistol. A preliminary study was also performed to evaluate the prevalence of OGSR in the general population as well as in a police laboratory environment. In the transfer study, results indicated that OGSR are not only transferred to the hand of the shooter, but also to other parts of the upper body. Thus, wrists and forearms also represent interesting targets as they are washed less frequently than hands. Samples from the face and hair of the shooters resulted in no OGSR detection just after firing. It was also observed that the concentrations recovered from clothing are generally higher compared to the same skin area. Prevalence in both general (n = 27) and police populations (n = 25) was low. No OGSR was detected in the samples from the general population and only two samples from the police population were found positive.